Electro-conductive 3D printed polycaprolactone/gold nanoparticles nanocomposite scaffolds for myocardial tissue engineering. (August 2022) - Ghaziof, Sharareh; Shojaei, Shahrokh; Mehdikhani, Mehdi; Khodaei, Mohammad; Jafari Nodoushan, Milad
Abstract: The human's heart cannot regenerate after a wound by itself. So myocardial tissue can be damaged, leading to acute inflammation and scar. To overcome this issue, three dimensional (3D) scaffolds with appropriate properties have been proposed. In this study, Poly ε-caprolactone (PCL)/Gold nanoparticles (GNPs) nanocomposite scaffolds containing 0, 0.25 and 0.5 wt% GNPs were prepared by 3-D printing by using Fused Deposition Modeling (FDM) technique. Scanning electron microscopy (SEM), Transmission electron microscopy (TEM), Fourier transform-infrared spectroscopy (FTIR-ATR), and X-ray diffraction (XRD) were then used to characterize the scaffolds. Also, mechanical properties, electrical conductivity, contact angle, and thermal behavior of the scaffolds were measured. According to the results, the scaffold containing 0.5 wt% GNPs corroborated optimal properties including appropriate mechanical properties, adequate wettability and suitable electrical conductivity for cardiovascular application, as compressive strength and electrical conductivity were increased approximately by 9.1% and 25%, respectively. In contrast, contact angle was decreased about 38%, which caused the scaffolds' hydrophilicity. Overall the electrocunductive 3D PCL/GNPs 0.5 wt% scaffold could be developed with the control of some parameters that could be well implemented by this fabrication method; also, the addition of GNPs to improve some properties can be regarded as a promising candidate for myocardial tissue engineering. Highlights: Polycaprolactone-gold nano particle (PCL-GNP) composite scaffold was fabricated using 3D printing. Fused Deposition Modeling (FDM) method was used for 3D printing of PCL-GNP composite. GNPs worked in combination with PCL and enhanced the electrical, mechanical and wettability properties of the scaffolds.